Implementation of Maternal Perinatal Surveillance and Response (AMP-SR) Audit in Indonesia: Scoping Review - Ninik Dwi Ambarwati; Martha Irene Kartasurya; Cahya Tri Purnami (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2023)
Surveillance and Response Maternal Perinatal Audit (AMP-SR) is a new guideline that is used as a reference for District/City, Provincial and National Health Offices in improving the quality of Maternal Perinatal Audit (AMP) in Indonesia, but the guideline has not worked well so it has an impact in the increase in cases of maternal mortality in Indonesia over the last three years from 87.93/100,000 Live Births (LB) in 2019 to 166.5/100,000 Live Births in 2021. Objective is to analyze evidence of AMP-SR implementation in districts/cities in Indonesia through scoping review. Articles were selected from six databases: Pubmed, Clinicalkey, Scopus, Springerlink, Science Direct, and Garuda with the inclusion criteria of original articles, full text, 2012-2022, Indonesian and English, research in Indonesia, qualitative, and relevant to research purposes. The keywords used are maternal death, policy, implementation, audit, Indonesia. Article screening was carried out with PRISMA. The SPIDER method was used to construct research questions.Of the 499 articles found, only seven articles met the inclusion criteria with a high eligibility value. Seven articles discuss the implementation of AMP-SR in Regencies/Cities in Indonesia with optimal Identification 57.14%, not optimal 42.86%. Reporting is optimal 28.57%, not optimal. The optimal review is 14.29%, not yet optimal 85.71%. The optimal response is 28.57%, not yet optimal 71.43%. Most of the implementation of AMP-SR in districts/cities in Indonesia is not optimal and is still constrained, so it is necessary to strengthen the role and commitment of health workers in implementing AMP-SR so that it is better and more comprehensive. Keywords: Audit, Implementation, Maternal Death, Policy